Establishing a new chronic pain clinic: challenges and achievements - Mohamed, Rozilah @ Abdul Hadi; Abdullah, Nor Zamzila; Othman, Norliza; Tajidin, Syazwani; Mohd Zanidin, Siti Nabilah; Mat Nor, Mohd Basri; Mohd Yatim, Asmarawati (2014)
Chronic pain is major public health problem that is associated with reduction in quality of life, poor psychological adjustment, physical disability, decreased income and high care cost which leads to great loss to the country. Patients suffering from chronic pain are in need of treatment and follow up from proper Chronic Pain Clinic. Unfortunately, the number of such facilities is limited as this area of expertise is rather new in Medicine. The objective of this paper is to share our experience on the challenges faced in the establishment of Chronic Pain Clinic in Tengku Ampuan Afzan Hospital, Kuantan, Pahang. This paper will describe the challenges that we have gone through from planning to the implementation of such clinic in 2009 and our achievement thus far. Administrative issues such as limited space and time, man power, financial support and resources are among majorchallenges faced apart from patients and management team's limitations. It is our future plan to include more disciplines in the management team as to ensure better patients' outcome towards a pain free hospital as envisaged by the Ministry of Health of Malaysia.